Resource Productivity in Milk Production on Mixed Dryland Farms in Nagaur District (RAJ.) - Vyas, D L (Annals of Arid Zone, 2016)
Resource productivity of dairy cows on dryland farms in Nagaur district of arid western Rajasthan was examined for 1977-78 to 1979-80. Fixed cost andÂ labour required subtractive corrective measures togetherwith appropriateÂ increases in feeds and fodder to improve the milk productivity on mixedÂ dryland farms.